PENGENDALIAN SERANGAN HAMA LALAT BUAH PADA INTENSITAS KERUSAKAN BUAH CABAI RAWIT (Capsicum frutescens L) DENGAN BAHAN PETROGENOL - Ni Komang Budiyani; I Wayan Sukasana (AGRICA, 2020)
Abstrack Cayenne pepper is a horticulture plant (vegetable) where the fruit is used for various food purposes. The decrease of the chilly yields productivity caused by several factors including the use of varieties with low yields and the attack of Plant Pests (OPT). Pests that often attack chili plants are fruit flies. Petrogenol could be used to control this pest.The method used was a randomized block design with 7 treatments and 3 replications by comparing the dose of petrogenol. The results showed that the D3 treatment showed the best parameters in the use of petrogenol doses in controlling fruit fly pests, in the parameters of healthy fruits, damaged fruit, insect catches, and damage intensity. The use of high doses of petrogenol can influence the trapping of fruit flies and as the control of fruit fly attacks Keywords : Fruit flies, cayenne pepper and petrogenol